Study on the measurement of high-quality development efficiency and influencing factors in the Yellow River Basin, China - Qin, Jianhui; Zhang, Fen; Zhu, Jiahao; Wu, Yuping (Scientific reports, 2025)
Environmental pollution and resource scarcity characterize the Yellow River Basin. Studying the factors of high-quality development efficiency (HQDE) and its spatial correlation in the Yellow River Basin is conducive to promoting the maximization of resource allocation in the Yellow River Basin. In this study, Super-EBM and Malmquist index were used to measure HQDE in the Yellow River Basin and explore its influencing factors. The results show that: (1) HQDE is higher in cities in the upper reaches of the Yellow River Basin than in the middle and lower reaches. Compared with the degree of technology utilization, the growth of HQDE mainly depends on technological progress. (2) The spatial correlation of urban HQDE decreases has been weakened annually. The high-efficiency cities in the upper reaches of the basin are obviously concentrated, while the middle and lower reaches of the confluence have both high- and low-efficiency cities located near each other. (3) HQDE has a negative geographical spillover effect. Regression analysis shows that energy consumption, economic development level, factor endowment, public awareness of environmental protection, and enterprise green level can promote the HQDE, while foreign investment utilization, environmental pollution, and education support have negative impacts on urban HQDE.